Stomach contents of channa striata and Clarias batrachus in the lake of UiTM Beting, Negeri Sembilan / Nur Nadhirah Arina Mad Jais - Mad Jais, Nur Nadhirah Arina (Faculty of Applied Sciences, 2014)
The aims of this study are to investigate the stomach contents and diet of two freshwater fishes which are Channa striata and Clarias batrachus in the lake of UiTM Beting, Negeri Sembilan. Furthermore, purpose of the study also concentrate on the number and prey composition consume by Channa striata and Clarias batrachus. Frequency of occurrence method, dominance method and points method are conducted to investigate the number and prey composition consume by these two types of freshwater fishes. There are six types of preys consumes by Channa striata, small shrimps, Gryllus sp. (crickets), Pantala sp. (dragonflies), Chara sp. (algae), Valanga sp. (grasshopper) and fish fry. Three prey types found consumes by Clarias batrachus, Chara sp. (algae), Gryllus sp. (cricket) and fish fry. The results show that 7 of 22 samples of Channa striata consume more on small shrimps which found abundant along the bank of the lake while 22 of 30 samples of Clarias batrachus feed mostly on Chara sp. which found abundant at the bottom and along the bank of the lake. Small shrimps are found consume by all size group of Channa striata while the percentage of food composition for Chara sp. consume by Clarias batrachus decrease as the size of fish increase.